Human Wharton’s jelly-derived mesenchymal stem cells express oocyte developmental genes during co-culture with placental cells - Asgari, Hamid Reza (Iran J Basic Med Sci, 2015)
OBJECTIVE(S): The present day challenge is how to obtain germ cells from stem cells to treat patients with cancer and infertility. Much more efforts have been made to develop a procedure for attaining germ cells in vitro. Recently, human umbilical cord-derived mesenchymal stem cells (HUMSCs) have been introduced with higher efficacy for differentiation. In this work, we tried to explore the efficacy of HUMSCs and some effective products of placental cells such as transforming growth factors. This study is aimed to optimize a co-culture condition for HUMSCs with placental cells to obtain primordial germ cells (PGCs) and reach into oocyte-like cells in vitro. MATERIALS AND METHODS: In this experimental study, HUMSCs and placental cells were co-cultured for 14 days without any external inducer in vitro. Then HUMSCs were assessed for expression of PGC markers; Octamer-binding transcription factor 4(OCT4), Tyrosine-protein kinase Kit (CKIT), Stage specific embryonic antigen 4 (SSEA4), DEAD (Asp-Glu-Ala-Asp) box polypeptide 4(DDX4) and oocyte specific markers; Growth differentiation factor-9(GDF9), Zona pellucida glycoprotein 3(ZP3). The pertinent markers were assessed by immunocytochemistry and Q-PCR. RESULTS: Co-cultured HUMSCs with placental cells (including amniotic and chorionic cells) presented Oct4 and DDX4, primordial germ cells specific markers significantly, but increment in expression of oocyte-like cell specific markers, GDF9 and ZP3 did not reach to statistically significant threshold. CONCLUSION: Placental cell supplements Transforming growth factor (TGF α, β) and basic fibroblast growth factor (bFGF) in a co-culture model can provide proper environment for induction of HUMSCs into PGCs and expression of oocyte-like markers.